PERSEPSI GERAKAN MAHASISWA NASIONAL INDONESIA (GMNI) CABANG SEMARANG TERHADAP MARHAENISME SEBAGAI IDEOLOGI PERJUANGAN - Ahmad Hasyemi Multizami; Warsito . .; Turtiantoro . . (Journal of Politic and Government Studies, 2017)
ABSTRACKIdologi Marhaenisme is a struggle born of a very deep process of reflection of Ir Soekarno on the condition of a nation that suffered from colonialism and capitalism a system that occurs in Region Geopolitics Indies. Marhaenisme born as an ideology that is used to change the misery with the achievement of the ideals of Socialism premises. Colonialism and Capitalism has been transformed into various forms and shapes in the life of the nation, but Marhaenisme remain as suatau means of resistance. Indonesian National Student Movement (GMNI) as a student organization, since it was first established in 1954 have pledged themselves to make Marhaenisme as an ideology of struggle. GMNI survive with all the conditions and the time of changing to remain faithful to hold fast to the teachings of Soekarno. But in the process of implementation, Marhaenisme often received criticism and questions that doubt appears logical process of Achieving Socialism. One satuya is happening in the region GMNI Semarang branch. So the authors conducted a study "Perceptions of Indonesian National Student Movement Semarang branch against Marhaenisme as Ideology Struggle". So that it can be seen GMNI members' perceptions regarding Marhaenisme new branch with the condition and the reality of what happened today.Keywords: Marhaenisme, Indonesian National Student Movement (GMNI), Chapter Semarang